Hemifacial Spasm in Mucopolysaccharidosis Type VI (Maroteaux–Lamy Syndrome). (1st June 2018) - Karir, Aneesh; Geraghty, Michael; Vassilyadi, Michael; Doja, Asif
Background: Hemifacial spasms are involuntary contractions of the muscles of one side of the face. Case Report: Here, we report a 5-year-old female patient with a significant past medical history, including mucopolysaccharidosis type VI, who also presented with hemifacial spasms. Further investigations showed narrowing of skull foramina and hydrocephalus, but no compression of the facial nerve. Carbamazepine was given to the patient, which caused cessation of the spasms. Discussion: Currently, there is no literature discussing the relationship between hemifacial spasms and mucopolysaccharidosis type VI; we have proposed that mucopolysaccharide deposits or dural thickening may contribute to nerve irritation.